Brewer’s spent grains protects against oxidative DNA damage in Saccharomyces cerevisiae - Moreira, Manuela M. (2017)
Brewer’s spent grain (BSG), obtained from barley malt during brewing, contains high amounts of phenolic acids, predominantly ferulic and p-coumaric acids. The protective effects of BSG extracts against oxidative DNA damage induced by H2O2 in Saccharomyces cerevisiae cells were investigated using an optimized yeast comet assay and flow cytometry. The results indicated that BSG extracts from black malt exhibited a 5-fold reduction in the genotoxic effects of H2O2, compared to the 2-fold decrease by the BSG extracts from pilsen malts. Flow cytometry analysis with dichlorofluorescein diacetate demonstrated that the intracellular oxidation of S. cerevisiae is also reduced to approximately 50% in the presence of 20-fold diluted BSG extracts. BSG extracts obtained from pilsen and black malt types exert dose-dependent protective properties against the genotoxic effects induced by ROS and decrease intracellular oxidation of yeast cells.